Analisis Faktor-Faktor Yang Membedakan Persepsi Mahasiswa Tentang Corporate Social Responsibility (Studi Empiris pada Universitas Diponegoro) - Deddy Sulestiyono (Politeknik Caltex Riau, 2020)
This study aims to examine the factors that influence students’ perceptions of Corporate Social Responsibility (CSR). In this study, measurement of the perception of test results performed on each variable consisting of gender, regional origin, and levels of education, with two different type of samples. Using survey data with questionnaire from two different type of samples, S1 and S2 students. The questionnaire consists of 19 questions. From the test results of the analysis in this study can be proven that variable level of education influence students’ perceptions on Corporate Social Responsibility, while the variable gender and regional origin do not affect students’ perceptions about CSR. Keywords : Corporate Social Responsibility, gender, regional origin, level of education